STRATEGIC FOUNDATIONS OF THE ORGANIZATION'S BUSINESS DEVELOPMENT IN CONDITIONS OF INCREASED EXISTENTIAL THREATS TO ECONOMIC SYSTEMS (Development Service Industry Management, 2024)
The article is devoted to topical issues of the development of modern business organizations in conditions of dynamism and instability of the external environment. Within the framework of the study, it was proved that the effective business development of the organization depends on the influence of external factors and the internal capabilities (potential) of the organization. The carried out classification of influencing factors allows determining the priority factors that determine the stability of a business organization in crisis conditions. On the basis of a comprehensive study, strategically important guidelines and specific strategies for the organization's business development were formed. The key strategies of anti-crisis development of the business organization are highlighted, taking into account the influence of crisis-forming factors. The author's concept of the strategic foundations of the business development of the organization in the conditions of increasing existential threats of economic systems, which involves a balanced coordination of the internal resources of the enterprise with the opportunities of the surrounding environment, has been formed. It has been proven that crisis manifestations act as an accelerator of business transformation and enable the formation of a larger sustainable business model for the development of the organization. Under the conditions of the deployment of crisis phenomena, the strategic priority should include the following strategies for the effective development of the organization: development and adaptation strategies, diversification of the organization's activities (product portfolio), stabilization and adaptation strategies, innovative and creative strategies for the development of business organizations. Strategic anti-crisis development of a modern organization should include a set of measures aimed at preserving stability, stability, increasing business capitalization, minimizing risks and strengthening the competitive positions of enterprises in crisis situations.In the course of the research, it was found that a significant gap in strategic anti-crisis management in business organizations of Ukraine is the lack of an analytical component, systematic business analysis, and a clear understanding of its tools. The process of anti-crisis strategic development should be based on an adaptive approach, taking into account the state of the organization itself and factors of the surrounding environment. Effective business development of the organization depends on the choice of optimal management solutions and strategic tools for overcoming crisis situations.
Keywords: anti-crisis development; strategy; business development of the organization; anti-crisis management; development strategies; anti-crisis strategy; proactive management; diversification; crisis; uncertainty; risk